Approaches to Understanding and Normative Definition of the Category “Cybercrime” and Related Concepts in the Practice of Regional International Organizations - L. M. Starkova (Московский журнал международного права, 2022)
INTRODUCTION. Against the background of the unfolding epidemic of coronavirus, the trends in cybercrime that appeared in previous years have reached unprecedented magnitudes. The rapid transfer of many basic spheres of social functioning to a digital platform in an actual legal vacuum provided criminals with almost unlimited opportunities. In these circumstances, the task of improving and unifying the basic categories in the field of combating the «new form of crime» is of paramount interest not only from the point of view of theory, but also in order to create an effective international legal mechanism to counter this threat.MATERIALS AND METHODS. The material for the study were legal documents developed under the auspices of 14 regional international organizations, which represent one or another regional group, scientific works of foreign and domestic scientists. The methodological basis of the study was the general scientific and private scientific methods of cognition, traditional for legal work.RESEARCH RESULTS. The study revealed inconsistencies in terminology, the absence of a uniformly understood and applied normative definition of a «new form of crime» and related concepts that would meet the criterion of authenticity. Regional international organizations operate with such concepts as "cybercrime", "attacks against information systems", "crimes in the field of computer information", "crimes in the field of information technology", "information crime", "crimes related to computers and networks", "digital security risks", "the use of information and communication technologies (ICTs) for terrorist and criminal purposes". All this indicates the absence of common approaches to understanding the very essence and specific features of this criminal phenomenon.DISCUSSION AND CONCLUSIONS. The author draws attention to the fact that the term "cybercrime" is used in 7 out of 14 groups of international documents of a regional nature. Analysis of the work of domestic and foreign researchers confirms the validity of the use of the term "cybercrime", as most fully and accurately reflecting the unique properties of this type of crime, its technical component. Based on the correlation and comparative study of the terms "information crime", "computer crime", "cybercrime", the author formulates basic provisions that can be taken into account when trying to develop a unified concept. The author draws attention to the fact that, taking into account the specific nature of the object, subject and virtual environment of committing these crimes, any legal norm should be formulated and correlated with the objective possibility of its practical implementation, taking into account technical characteristics.